On a Class of Neumann Boundary Value Equations Driven by a (p1, , Pn)-Laplacian Operator (Journal of Partial Differential Equations, 2012)
In this paper we prove the existence of an open interval (λ' ,λ") for each λ in the interval a class of Neumann boundary value equations involving the (p_1,..., p_n)- Laplacian and depending on λ admits at least three solutions. Our main tool is a recent three critical points theorem of Averna and Bonanno [Topol. Methods Nonlinear Anal. [1] (2003) 93-103].
Keywords: (p_1; ...; p_n)-Laplacian; Neumann problem; three solutions; critical points; multiplicity results